The 6M Classification of Nutrients - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Nutrition is a complex and sometimes confusing subject.The existing classification of nutrients into two groups,macro and micronutrients, does not do justice to the widespectrum of nutritional foods available. In this opinionpiece, we suggest a six-layered 6M hierarchal classificationof nutrients that offers a comprehensive and completeunderstanding of nutrition. Mega, macro, meso, micro,micro-bio, and minimization of anti-nutrients make up the6M list of nutrients. Keywords: Diabetes, medical nutrition therapy, nutrition,obesity